Assessment of apoptosis in breast cancer results of study semithin sections and electron microscopy - Mniкhovich M. V. (Морфологія / Morphologia / Morfologìâ, 2011)
The article describes the evaluation of one form of programmed cell death – apoptosis. Discussed the possibility of morphological verification of the process of apoptosis. Shown that the "gold standard" of research is the study of apoptosis in semithin sections, followed by electron microscopy. It is shown that in infiltrative ductal breast cancer, intensive process of apoptosis takes place in a close relationship with the process of mitosis. In various parts of the tumor node ductal breast cancer apoptosis percolationem unevenly. Detectedabnormality of apoptosis in ductal breast cancer, which manifests itself in the absence of phagocytosis of apoptotic bodies.